The Effects of Immersive Virtual Reality Applications on Enhancing the Learning Outcomes of Undergraduate Health Care Students: Systematic Review With Meta-synthesis - Justina Yat Wa Liu; Yue-Heng Yin; Patrick Pui Kin Kor; Daphne Sze Ki Cheung; Ivy Yan Zhao; Shanshan Wang; Jing Jing Su; Martin Christensen; Stefanos Tyrovolas; Angela Y M Leung (JMIR Publications, 2023)
BackgroundImmersive virtual reality (IVR) applications are gaining popularity in health care education. They provide an uninterrupted, scaled environment capable of simulating the full magnitude of sensory stimuli present in busy health care settings and increase students' competence and confidence by providing them with accessible and repeatable learning opportunities in a fail-safe environment. ObjectiveThis systematic review aimed to evaluate the effects of IVR teaching on the learning outcomes and experiences of undergraduate health care students compared with other teaching methods. MethodsMEDLINE, Embase, PubMed, and Scopus were searched (last search on May 2022) for randomized controlled trials (RCTs) or quasi-experimental studies published in English between January 2000 and March 2022. The inclusion criteria were studies involving undergraduate students majoring in health care, IVR teaching, and evaluations of students' learning outcomes and experiences. The methodological validity of the studies was examined using the Joanna Briggs Institute standard critical appraisal instruments for RCTs or quasi-experimental studies. The findings were synthesized without a meta-analysis using vote counting as the synthesis metric. A binomial test with P<.05 was used to test for statistical significance using SPSS (version 28; IBM Corp). The overall quality of evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation tool. ResultsA total of 17 articles from 16 studies totaling 1787 participants conducted between 2007 and 2021 were included. The undergraduate students in the studies majored in medicine, nursing, rehabilitation, pharmacy, biomedicine, radiography, audiology, or stomatology. The IVR teaching domains included procedural training (13/16, 81%), anatomical knowledge (2/16, 12%), and orientation to the operating room setting (1/16, 6%). The quality of the 75% (12/16) of RCT studies was poor, with unclear descriptions of randomization, allocation concealment, and outcome assessor blinding procedures. The overall risk of bias was relatively low in the 25% (4/16) of quasi-experimental studies. A vote count showed that 60% (9/15; 95% CI 16.3%-67.7%; P=.61) of the studies identified similar learning outcomes between IVR teaching and other teaching approaches regardless of teaching domains. The vote count showed that 62% (8/13) of the studies favored using IVR as a teaching medium. The results of the binomial test (95% CI 34.9%-90%; P=.59) did not show a statistically significant difference. Low-level evidence was identified based on the Grading of Recommendations Assessment, Development, and Evaluation tool. ConclusionsThis review found that undergraduate students had positive learning outcomes and experiences after engaging with IVR teaching, although the effects may be similar to those of other forms of virtual reality or conventional teaching methods. Given the identification of risk of bias and low level of the overall evidence, more studies with a larger sample size and robust study design are required to evaluate the effects of IVR teaching. Trial RegistrationInternational prospective register of systematic reviews (PROSPERO) CRD42022313706; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=313706